2008
DOI: 10.1007/s00455-007-9143-y
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Lip Force Measurement in Healthy Controls and in Patients with Stroke: A Methodologic Study

Abstract: A prefabricated oral screen has shown promising results as a muscle self-training device to improve the lip function of stroke patients affected by oropharyngeal dysphagia. However, a technique for the measurement of lip muscle force, whether in healthy individuals or in stroke patients, is lacking. The present study was designed to (1) test the intra- and interreliability of lip force measurements by means of a newly devised Lip Force Meter, LF100, (2) determine a normal lower limit for lip force in newtons (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 15 publications
3
70
0
Order By: Relevance
“…Their results indicated a decrease in orofacial muscle activity during oral functions but no significant change in tooth position. Hä gg et al [15] found in a retrospective study that self-training with an oral screen could improve lip force and swallowing capacity in stroke patients with oropharyngeal dysphagia. It was concluded that the treatment results were more likely attributable to sensory motor stimulation and the plasticity of the central nervous system, than the training of the lip muscles per se.…”
Section: Introductionmentioning
confidence: 98%
“…Their results indicated a decrease in orofacial muscle activity during oral functions but no significant change in tooth position. Hä gg et al [15] found in a retrospective study that self-training with an oral screen could improve lip force and swallowing capacity in stroke patients with oropharyngeal dysphagia. It was concluded that the treatment results were more likely attributable to sensory motor stimulation and the plasticity of the central nervous system, than the training of the lip muscles per se.…”
Section: Introductionmentioning
confidence: 98%
“…During training, the screen was inserted predentally behind closed lips and the patient had to sit in a chair or in the bed with the body in a strictly upright position, with support for the head. The patient had to hold the screen against the horizontal gradually increasing pulling pressure for 5-10 s while trying to resist the force by tightening the lips and pressing the head backward against a head rest [16,17,21]. The exercise was performed 3 times per session before eating, 3 times daily.…”
Section: Oral Screen (Os) Trainingmentioning
confidence: 99%
“…It improves the contact between tongue and palate, raises the tip of the tongue, helps the tongue to contract upward and backward, activates the levator anguli oris muscles (VII), the zygomaticus minor and major muscles, and the buccinator muscles, thus indirectly improving oropharyngeal swallowing [10,14,25]. PP was the first to be applied to sensorimotor training in dysphagia studies [14,15]; the OS device has more recently been introduced [16,17,21]. The OS training (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Patients were seated in a stable position and instructed to keep the oral screen inside their lips while the examiner pulled the handle. The LF100 instrument recorded the maximum value measured during 10 seconds.…”
Section: Lip Forcementioning
confidence: 99%